The Effect of Students' Perceptions of Career Information Services on Students’ Career Decision Making Self-Efficacy - Haryati, Umi; Purwanto, Edy; Awalya, Awalya (Universitas Negeri Semarang, 2021)
Lack of information related to education, position, or work that matches students' abilities is one of the obstacles that cause students unable to make appropriate career decisions. The purpose of this study was to empirically examine the effect of students' perceptions of career information services on career decision making self-efficacy. It involved 108 SMK students selected by quota random sampling technique. The data analysis technique used was simple linear regression analysis with the help of SPSS 24. The results showed that there was a significant relationship between students' perceptions of career information services on career decision making self-efficacy by 16% (β = 0.40, p < 0.01). The quality of good career information services will affect the self-efficacy of good career decision making.